Growth Response and Yields of Variety of Sorghum on Multiple NPK Fertilization in Dry Land - Samanhudi, Samanhudi; Harsono, Puji; Hartati, Sri; Iswahyudi, Iswahyudi; Wicaksono, Naufal Ghazy (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2024)
Land degradation is a major constraint to agricultural productivity, with drylands particularly vulnerable to critical conditions. Sorghum (Sorghum bicolor L. Moench) is a promising crop for such environments due to its adaptability and dual-purpose value for both biomass and sugar-rich stalks. This study evaluated the growth and yield response of four sorghum varieties—Super, Suri, Numbu, and Keller—to different rates of compound NPK fertilizer under dryland conditions. The experiment was arranged in a Randomized Complete Block Design (RCBD) with two factors: sorghum varieties and five fertilizer doses (0, 10, 12, 14, and 16 g plant⁻¹), replicated three times. Data were subjected to ANOVA, and treatment means were compared using DMRT at the 5% significance level. Results showed that the Keller variety consistently produced the best agronomic performance, including plant height, number of leaves, stem segments, stem diameter, and biomass dry weight. Moreover, Keller combined with 12 g plant⁻¹ of NPK fertilizer produced the highest sap content (14.0% Brix), highlighting its potential as a dual-purpose sorghum. Leaf traits were most responsive at 14 g plant⁻¹, indicating that moderate-to-high fertilization enhances vegetative growth without excessive input. These findings demonstrate that varietal selection coupled with appropriate nutrient management is crucial for optimizing sorghum production in dryland systems. The study provides practical guidance for farmers and can inform future breeding and fertilizer recommendation programs for sustainable sorghum cultivation.